TUTORING EDUCATION FRANCHISE STRATEGY IN INDONESIA: A SWOT ANALYSIS - Benny R. P. Sinaga (Scientia Integritas Utama, 2022)
Tutoring is one of the basic needs for parents who want the best education for their children. In order to reach the entire territory of the Unitary State of the Republic of Indonesia in producing equitable quality education, it is necessary to conduct an internal and external environmental analysis (SWOT analysis). Based on a literature study, Tutoring must implement a SWOT analysis strategy annually from year to year. In winning the competition in the franchise system, Tutoring needs to increase investment in information technology, internalize values to make the organizational structure more efficient and flexible, and strengthen and improve the clauses of the franchise contract by strengthening the reward and punishment system.